RNA Expression Profile and Potential Biomarkers in Patients With Spinocerebellar Ataxia Type 3 From Mainland China - Li, Tianjiao; Hou, Xiaocan; Chen, Zhao; Peng, Yun; Wang, Puzhi; Xie, Yue; He, Lang; Yuan, Hongyu; Peng, Huirong; Qiu, Rong; Xia, Kun; Tang, Beisha; et al. (Frontiers in Genetics, 2019)
lncRNAs play an important role in growth, development, and reproduction, undoubtedly contributing to pathogenesis and progression of diseases. The emerging evidences have proven the involvement of the lncRNAs as a regulatory factor in diseases, such as some neurodegenerative diseases. Spinocerebellar Ataxia Type 3/Machado-Joseph Disease (SCA3/MJD) has a prominent prevalence in China. Given that little information is available for the contribution of the lncRNAs to the pathogenesis of the SCA3/MJD, as a pilot study, we investigated the expression profile of lncRNAs by high-throughput sequencing from 12 patients and 12 healthy individuals. The sequencing results showed 5540 of the known and 2,759 of the novel lncRNAs. Six lncRNAs were confirmed to be statistically significant in PBMCs between the SCA3/MJD patients vs. healthy individuals, and further validated in cerebellar tissues. Based on these results, the NONHSAT022144.2 and NONHSAT165686.1 might be involved in the pathogenesis of SCA3/MJD and may become the potential biomarkers for the SCA3/MJD. Other 4 novel lncRNAs together with NONHSAT022144.2 and NONHSAT165686.1 make a plus to the expression profile of lncRNA.